2017
DOI: 10.11648/j.ajbls.20170502.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Energy of Consciousness Healing Treated <i>Withania Somnifera</i> (Ashwagandha) Root Extract Using LC-MS, GC-MS, and NMR Spectroscopy

Abstract: Abstract:Withania somnifera (Ashwagandha) root extract is very useful herbal medicine since from ancient time. The current study designed to investigate the impact of The Trivedi Effect ® -Energy of Consciousness Healing Treatment on the structural properties of the ashwagandha root hydroalcoholic extract using LC-MS, GC-MS, and NMR spectroscopy. Ashwagandha root extract was divided into two parts -one part was control (without treatment), while other part was treated with the Energy of Consciousness Healing T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Biofield Energy Treatment leads to receive the energy by the object and respond in a useful way, while The Trivedi Effect ® has been reported with the significant discovery in both living organisms and nonliving materials. The Trivedi Effect ® has been described with significant transformation in the physicochemical properties of metals, chemicals, ceramics and polymers [18][19][20][21][22], improved agricultural crops overall productivity, yield and quality by several folds [23][24], altered antimicrobial characteristics of pathogenic microbes at genetic level [25][26][27], improved activity of nutraceutical compounds [28,29], livestock [30], and many more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofield Energy Treatment leads to receive the energy by the object and respond in a useful way, while The Trivedi Effect ® has been reported with the significant discovery in both living organisms and nonliving materials. The Trivedi Effect ® has been described with significant transformation in the physicochemical properties of metals, chemicals, ceramics and polymers [18][19][20][21][22], improved agricultural crops overall productivity, yield and quality by several folds [23][24], altered antimicrobial characteristics of pathogenic microbes at genetic level [25][26][27], improved activity of nutraceutical compounds [28,29], livestock [30], and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported in the literature that The Trivedi Effect ® has the significant capability to alter the physicochemical and thermal properties of various pharmaceuticals, nutraceuticals, and organic compounds through possible intervention of neutrinos [31,28]. The Trivedi Effect ® -Consciousness Energy Healing Treatment would be a useful approach for the enhancement of the bioavailability of pharmaceuticals and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) is drawing importance in several fields include material science [12], pharmaceuticals [13], nutraceuticals [14], organic compounds [15,16], microbiology [17], agricultural [18], biotechnology [19], genetics [20], medical [21] due to its amazing ability for modification of the characteristic properties of the numerous non-living and living substances. Recently literature reported that The Trivedi Effect ® -Energy of Consciousness Healing Treatment has the astounding capability to alter physicochemical properties such as crystalline structure, crystallite size, particle size, surface area, and thermal stability of various nutraceuticals such as herbal medicines, minerals through introducing a new polymorph [22][23][24][25][26]. It is assumed that Biofield Energy Treated pharmaceutical/nutraceutical compounds would be beneficial for enhancement of their therapeutic efficacy against the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported in the literature that The Trivedi Effect ® has the significant capability to alter the physicochemical and thermal properties of various pharmaceuticals, nutraceuticals, and organic compounds through possible intervention of neutrinos [31][32][33]. The Trivedi Effect ® -Consciousness Energy Healing Treatment would be a useful approach for the enhancement of the bioavailability of pharmaceuticals and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%